Medial Open-Wedge High Tibial Osteotomy with Partial Meniscectomy and Without Cyst Excision for Popliteal Cysts: A Case Series - Kang-Il Kim; Jun-Ho Kim (Biomedicines)
Introduction: Popliteal cysts (PCs) are occasionally accompanied by knee osteoarthritis (OA) and varus malalignment. However, whether concomitant arthroscopic excision of PCs with medial open-wedge high tibial osteotomy (MOWHTO) improves the osteoarthritic environment remains unclear. Therefore, this study assessed serial changes in C-size, medial meniscus extrusion (MME), and cartilage status for up to 2 years following an MOWHTO. Methods: This study retrospectively used serial magnetic resonance imaging (MRI) evaluations to assess 26 consecutive patients who underwent MOWHTO. Of the 26 patients, six with preoperative PCs were included. Based on the arthroscopic findings at the time of the MOWHTO, concomitant meniscal and chondral lesions, and whether or not partial meniscectomy was performed, were evaluated. All patients underwent second-look arthroscopy with plate removal 2 years postoperatively. The PC size, MME, and cartilage sub-scores in the medial compartment of the whole-organ MRI score (WORMS) were assessed by serial MRI preoperatively and at 3, 6, 18, and 24 months postoperatively. The recurrence of PCs and clinical outcomes, including the Rauschning–Lindgren grade, were also evaluated when serial MRI was performed. Moreover, changes in cartilage status were assessed using two-stage arthroscopy. Results: All patients underwent concomitant partial meniscectomy for medial meniscal tears in the posterior horn. A significant decrease in the mean size of preoperative PCs (27.4 ± 22.3 mm) was noted from 3 months postoperatively (8.7 ± 7.6 mm, p = 0.018), and thereafter. The mean size of PCs further decreased with time until 2 years (1.5 ± 4.0 mm, p = 0.018) following an MOWHTO with partial meniscectomy. Moreover, significant improvements in the MME and WORMS values were noted from 3 to 24 months postoperatively. Meanwhile, no PC recurrence occurred during the follow-up period and the preoperative Rauschning–Lindgren grade improved significantly with time after MOWHTO (p = 0.026). Furthermore, the two-stage arthroscopic assessments showed significant improvements in ICRS grade in the medial femoral condyle (p = 0.038). Conclusions: After an MOWHTO with partial meniscectomy, PCs decreased with time up to 2 years postoperatively; no recurrence occurred during the follow-up period, although cyst excision was not concomitantly performed. Furthermore, the reduction in PCs corresponded with improvements in MME and chondral lesions in the knee joint following the MOWHTO.